Produksi Pemindangan Ikan Tongkol Variasi Konsumsi Olahan untuk Meningkatkan pendapatan Masyarakat Gampong Aceh Kabupaten Aceh Timur - Fitriani, Rini; Zulfiani; Suri Amilia (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The aim of this program is to empower the community to make tuna pindang products, provide motivation to produce tuna pindang to help increase people's income and contribute to the development of tuna tuna business in Gampong Aceh. The methods to be used in Community Service activities are the observation method, practice method and lecture method. Community participation is very important in the success of this PKM program. It is hoped that the community will be able to take part in this activity starting with the desire to empower active and sustainable working groups of housewives, the community taking part in product manufacturing and packaging counseling, the community jointly making pindang cob products which will become their trademark from Gampong Aceh, Kabupaten Aceh Timur, and the community can market their products which extend to other areas. Problems in empowering the Gampong Aceh community to become a productive community in processing the available natural resources into superior products and are the hallmark of Gampong Aceh. The abundance of tuna has not yet been produced by doing pemindangan, by assisting the people of Gampong Aceh to make tuna processing into a savory variation of processed tuna fish, hopefully it will be in great demand by the community. After the cob fish processing is done, it will be packaged in attractive and hygienic packaging so that it becomes an attraction for the market share.